Screening and characterization of indigenous yeast strains from spontaneously fermented strawberry (Fragaria × ananassa Duchesne) juice for potential wine production - Ying Mao; Qingfang Xu; Weiliang Liu; Xiu Gao; Lifang Zhang; Qin Zhu; Jian Cai; Ling Zhu (Archives of Microbiology, 2026)

137Cs and 210Pbex dating to assess sedimentation rates in terraced valley floor fields - Yunqi Zhang; Shucui Liu; Dan Li; Wei Li; Qingfang Tan; Yi Long; Guirong Hou; Ziteng Luo; Haiyan Yi; Yong Wang; Bo Tan (Journal of Hydrology, 2026)

Fungal community succession and its association with volatile flavor compounds during natural fermentation of Rubus ellipticus wine - Ling Zhu; Kexin Wang; Qingfang Xu; Xiu Gao; Weiliang Liu; Qin Zhu; Lifang Zhang; Yupeng Liang; Jian Cai (Food Bioscience, 2026)

Molecular phylogeny and taxonomy of Mus pahari (Rodentia: Muridae) - Qingfang Zou; Lin Gu; Tao Zhang; Chengxin Zhou; Xuming Wang; Tong Zhang; Keji Guo; Shaoying Liu; Shunde Chen (Mammalian Biology, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

Construction of photothermal hydrogel with sunlight internal reflection function for improving solar seawater evaporation efficiency - Shenghua Lv; Ying Chen; Shida Zhao; Wei Liu; Qingfang Zhou; Ruijun Gao (Chemical Engineering Journal, 2026)

Optimizing fertilizer and planting density to stabilize yields and improve water use efficiency in rain-fed wheat–maize rotations - Xueni Yang; Shujie Sun; Haocong Li; Ziyan Guo; Chi Ma; Bo Liu; Wei Zhang; Ruixia Ding; Peng Zhang; Tiening Liu; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2026)

Interaction mechanism between infill walls and prestressed self-centering frames - Yujie Lu; Juewen Wang; Qingfang Lv; Ye Liu; Jun Xu; Huanlong Ding (Engineering Structures, 2026)

Carbon sphere template derived TiO2 hollow sphere with nitrogen doping and carbon sensitization for visible-light driven cyclohexane oxidation and tetracycline hydrochloride degradation - Guang Xu; Ying Zhang; Changyou Lu; Dongxuan Guo; Lina Liu; Qingfang Deng; Shangkun Ma; Xin Wang (Journal of Water Process Engineering, 2025)

Coplanar DCA-based hypofractionated stereotactic radiotherapy for very small brain metastasis from non-small cell lung cancer: treatment planning comparison with coplanar VMAT and preliminary clinical outcome - Shipai Zhu; An Li; Jia Liu; Qin Deng; Qingfang Li; Jialu Lai; Lin Zhou (Physical and Engineering Sciences in Medicine, 2025)

β,β-Dimethylacrylshikonin Alleviates Zebrafish (Danio rerio) Soyasaponin-Induced Enteritis by Maintaining Intestinal Homeostasis and Improving Intestinal Immunity and Metabolism - Ming Liu; Xin Lu; Leong-Seng Lim; Yinhui Peng; Lulu Liu; Kianann Tan; Peng Xu; Mingzhong Liang; Yingrui Wu; Qingfang Gong; Xiaohui Cai (Fishes, 2025)
Soyasaponin intolerance is common in ancient fish species, making them susceptible to enteritis caused by dietary soybean meal. β,β-Dimethylacrylshikonin is the key active monomer found in Lithospermum erythrorhizon and is known for its multiple pharmacological activities. However, its effect on soybean meal-induced enteritis remains unknown. The administration of 2 g/kg of β,β-Dimethylacrylshikonin (LE) effectively alleviated 5 g/kg of soyasaponin-induced histopathological changes and dysfunction, as evidenced by the expression of inflammation-related genes (il-1β, il-8, and il10). Regarding the gut microbiota composition, LE therapy decreased the population of inflammation-linked Proteobacteria and concurrently elevated the proportion of Fusobacteriota, effectively sustaining the balance of the zebrafish gut microbiota. Moreover, at the genus level, LE treatment also increased the abundance of Cetobacterium. Transcriptional results suggested that LE intervention mainly regulated immune-related pathways, including cytokine–cytokine receptor interaction, the TGF-beta signaling pathway, taurine and hypotaurine metabolism, and arachidonic acid metabolism. In conclusion, 5 g/kg of soyasaponins caused intestinal injury in zebrafish, and β,β-Dimethylacrylshikonin can reduce intestinal inflammation by regulating the intestinal microbial balance and metabolic disorder, with the best effect at 2 g/kg.

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

From biodegradation to biohazard: Polylactic acid microplastics induced rice growth inhibition in agroecosystems - Bigui Lin; Qingfang Fan; Fang Liu; Luya Wang; Chaoxian Wei; Beibei Liu; Juan Zhao; Linzi Zuo; Yi Xie (Journal of Hazardous Materials, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

Organic matter accelerated microbial iron reduction and available phosphorus release in reflooded paddy soils - Xipeng Liu; Yuchen Shu; Kejie Li; Haotian Wang; Qingfang Bi; Haibo Wang; Chengliang Sun; Xianyong Lin (Soil Ecology Letters, 2025)

High-temperature pressure cooking on the quality of Basa (Pangasius bocourti) fish maw: Gelling, in vitro digestion and proteomic analysis - Shiyu Wu; Qiuyu Lu; Lianying Xu; Shengnan Zhan; Wenge Yang; Qingfang Ying; Haixia Yu; Ying Liu; Tao Huang (Food Chemistry, 2025)

Correction to: Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Decoding the aroma changes of stir-fried shredded potatoes with different soy sauces using thermal desorption combined with gas chromatography–mass spectrometry and sensory evaluation - Ruixin Meng; Dandan Pu; Zikang Xu; Jinchang Liu; Qingfang Zhang; Maosheng Xu; Baoguo Sun; Yuyu Zhang (Food Chemistry, 2025)

Hydrolysis and methane yield enhancement of anaerobic co-digestion of kitchen waste and sewage sludge by air/carbon dioxide nanobubble water - Qingfang Zhang; Jiazi Niu; Peilin Guo; Jie Wang; Cheng Peng; Yifan Zhang; Zhe Liu; Yabian Wang; Liyang Xue; Tianfeng Wang (Fuel, 2025)

Does fiscal decentralization reduce air pollution: Evidence from Qinghai-Tibet Plateau - Jianhui Xu; Ning Ruan; Qingfang Liu; Xiantian Zhang; Jinping Song; Jialiang Xie (Journal of Cleaner Production, 2025)

Effects of Sophora flavescens ethanol extract supplementation in high soybean meal diets on growth, intestinal antioxidant status and immune response in Pearl Gentian grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Xin Lu; Yinhui Peng; Kianann Tan; Bingxiang Zhou; Qingfang Gong; Peng Xu; Xueying Liang; Wenjie Liu; Kit Yue Kwan; Yingrui Wu; Xiaohui Cai (Aquaculture International, 2025)

Study of condensable particulate matter from stationary combustion sources: Source profiles, emissions, and impact on ambient fine particulate matter - Huanhuan Tong; Yangjun Wang; Ling Huang; Qingfang Su; Xin Yi; Hehe Zhai; Sen Jiang; Hanqing Liu; Jiaqiang Liao; Li Li (Science of The Total Environment, 2024)

Effects of Sophora flavescens dietary supplementation on the growth performance, haematological indices, and intestinal bacterial community of Oreochromis niloticus - Xin Lu; Yingrui Wu; Yinhui Peng; Wenjie Liu; Ming Liu; Peng Xu; Kianann Tan; Xueying Liang; Xiaohui Cai; Qingfang Gong (Journal of Fish Biology, 2024)
Sophora flavescens is considered to be of various medicinal and economic importance. Previous studies have shown that it has antibacterial, antioxidant, and immune‐enhancing functions. To explore the full potential of S. flavescens in fish feed development, we investigated the effects of different levels of S. flavescens added to the diet on the growth performance, haematological indices, and the intestinal bacterial community of Nile tilapia ( Oreochromis niloticus ). The feeding trial lasted for 56 days, and the initial weight of the fish was 40.00 ± 5.00 g. Nile tilapia were randomly divided into six groups: a control group (CN) and five S. flavescens supplementation groups (0.02%, 0.04%, 0.08%, 0.16%, and 0.3% [w/w] of S. flavescens in diet). The growth performance of fish increased first and then decreased with the increase of S. flavescens supplemental level. Compared with other experimental groups, the growth performance of fish supplemented with 0.08% S. flavescens was significantly improved ( p S. flavescens , reaching the highest level at 0.08% ( p S. flavescens and reached the lowest value at 0.08% ( p S. flavescens was 0.04% in each treatment group ( p Bacteroides dominated the gut communities, and compared with the control group, two uncultured bacteria were suppressed. In addition, when the supplemental level of S. flavescens was more significant than 0.04%, the proliferation of Arcobacter cryaerophilus , Solibacillus silvestris , and Escherichia sp. in the gut of Nile tilapia was promoted. The results revealed that S. flavescens , as an additive to the Nile tilapia diet with levels ranging from 0.04% to 0.08%, can enhance the growth performance and immunity and promote the proliferation of intestinal beneficial bacteria of Nile tilapia.

Hysteresis performance and damage mode of self-centering frame with masonry infill wall: Experimental study assisted with DIC technique - Yujie Lu; Qingfang Lv; Ye Liu (Engineering Structures, 2024)

Isolation and identification of epiphytic Pichia kudriavzevii from loquat peels and investigation of its fermentation characteristics for liquor production - Qingfang Xu; Wei Huang; Yanqin Li; Jian Cai; Xiu Gao; Xu Bai; Weiliang Liu; Lifang Zhang; Ling Zhu (Archives of Microbiology, 2024)

The long-term nitrogen fertilizer management strategy based on straw return can improve the productivity of wheat-maize rotation system and reduce carbon emissions by increasing soil carbon and nitrogen sequestration - Ziyan Guo; Yang Liu; Xiangping Meng; Xueni Yang; Chi Ma; Huina Chai; Hui Li; Ruixia Ding; Khudayberdi Nazarov; Xudong Zhang; Qingfang Han (Field Crops Research, 2024)

Experimental study on the hysteretic performance of a self-centering frame infilled with a bamboo wall - Yujie Lu; Ye Liu; Qingfang Lv (Engineering Structures, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Impact path of digital economy on carbon emission efficiency: Mediating effect based on technological innovation - Chengzhen Song; Qingfang Liu; Jinping Song; Wei Ma (Journal of Environmental Management, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Exosomes from porcine serum as endogenous additive maintain function of boar sperm during liquid preservation at 17 °C in vitro - Yang Wang; Qimin Liu; Qingfang Sun; Lijuan Zheng; Tianqi Jin; Heran Cao; Chao Zhu; Long Li; Ye Gong; Fangxia Yang; Wuzi Dong (Theriogenology, 2024)

Antidote or poison? Digital economy and land-use - Qingfang Liu; Huaxiong Jiang; Jianmei Li; Jinping Song; Xiantian Zhang (Land Use Policy, 2024)

Recovery and characterization of β-glucosidase-producing non-Saccharomyces yeasts from the fermentation broth of Vitis labruscana Baily × Vitis vinifera L. for investigation of their fermentation characteristics - Ling Zhu; Xuemei Zhang; Yuchen Wang; Xiu Gao; Qingfang Xu; Weiliang Liu; Qihe Xu; Dongmei Zhao; Jian Cai (Archives of Microbiology, 2024)

Spatial correlation and allometric growth relationship between economic development and carbon emission in Lanzhou–Xining urban agglomeration - Qingfang Liu; Jinping Song; Teqi Dai; Huiran Han; Jianhui Xu; Jianmei Li; Enru Wang (Environment, Development and Sustainability, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

An urban planning perspective on enhancing electric vehicle (EV) adoption: Evidence from Beijing - Huaxiong Jiang; Haoran Xu; Qingfang Liu; Liang Ma; Jinping Song (Travel Behaviour and Society, 2024)

Experimental evaluation of fracture toughness of bamboo fiber reinforced high performance lightweight aggregate concrete - Jing Shi; Yujie Lu; Ran Zhu; Ye Liu; Yu Zhang; Qingfang Lv (Engineering Structures, 2023)

Identification of genomic-wide genetic links between cutaneous melanoma and obesity-related physical traits via cFDR - Shen Lin; Runnan Shen; Jingqian Huang; Yanhan Liu; Hongpeng Li; Qingfang Xu (Genes & Genomics, 2023)

The allometric relationship between carbon emission and economic development in Yangtze River Delta: fusion of multi-source remote sensing nighttime light data - Jianhui Xu; Qingfang Liu; Ning Ruan; Feng Hu; Weizhong Jiang; Yuanyuan Li; Wenhao Ma (Environmental Science and Pollution Research, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Exploring the relationship between deep roots and shoot growth of wheat under different soil moisture: A large soil column experiment 1 - Dan Liu; Siwei Mou; Yufeng Zou; Baoping Yang; Ruixia Ding; Junfeng Nie; Xudong Zhang; Zhikuan Jia; Qingfang Han (Rhizosphere, 2023)

Tissue-resident immune cells in the pathogenesis of multiple sclerosis - Jie Tian; Lingli Jiang; Zixiang Chen; Qingfang Yuan; Chang Liu; Longfeng He; Feng Jiang; Ke Rui (Inflammation Research, 2023)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Microbial respiratory thermal adaptation is regulated by r‐/K‐strategy dominance - Hongyang Chen; Qingfang Jing; Xiang Liu; Xuhui Zhou; Changming Fang; Bo Li; Shurong Zhou; Ming Nie (Ecology Letters, 2022)
Microbial thermal adaptation is considered to be one of the core mechanisms affecting soil carbon cycling. However, the role of microbial community composition in controlling thermal adaptation is poorly understood. Using microbial communities from the rhizosphere and bulk soils in an 8‐year warming experiment as a model, we experimentally demonstrate that respiratory thermal adaptation was much stronger in microbial K ‐strategist‐dominated bulk soils than in microbial r ‐strategist‐dominated rhizosphere soils. Soil carbon availability exerted strong selection on the dominant ecological strategy of the microbial community, indirectly influencing respiratory thermal adaptation. Our findings shed light on the linchpin of the dominant ecological strategy exhibited by the microbial community in determining its respiratory thermal adaptation, with implications for understanding soil carbon losses under warming.

Association of a novel antisense lncRNA TP73-AS1 polymorphisms and expression with colorectal cancer susceptibility and prognosis - Jiayao Fan; Huiqing Xu; Bing Liu; Fangyuan Jing; Qingfang He; Shasha Zheng; Haining Shi; Lefei Jiao; Chunhong Fan (Genes & Genomics, 2022)

Spatiotemporal variation in near-surface CH4 concentrations in China over the last two decades - Jianhui Xu; Qingfang Liu; Kai Wang; Qiulong Wang; Li Wang; Yuchan Liu; Maoyu Li (Environmental Science and Pollution Research, 2021)

Calculation of instream ecological water requirements under runoff variation conditions: Taking Xitiaoxi River in Taihu Lake Basin as an example - Qin Wang; Shuwen Wang; Qingfang Hu; Yintang Wang; Yong Liu; Lingjie Li (Journal of Geographical Sciences, 2021)

Hormonal changes with uniconazole trigger canopy apparent photosynthesis and grain filling in wheat crop in a semi-arid climate - Irshad Ahmad; Muhammad Kamran; Xiangping Meng; Shahzad Ali; Shakeel Ahmad; Zhiqiang Gao; Tiening Liu; Qingfang Han (Protoplasma, 2021)

Effects of Plant Growth Regulators on Seed Filling, Endogenous Hormone Contents and Maize Production in Semiarid Regions - Irshad Ahmad; Muhammad Kamran; Xiangping Meng; Shahzad Ali; Bayasgalan Bilegjargal; Tie Cai; Tiening Liu; Qingfang Han (Journal of Plant Growth Regulation, 2019)

Application of Uniconazole Improves Photosynthetic Efficiency of Maize by Enhancing the Antioxidant Defense Mechanism and Delaying Leaf Senescence in Semiarid Regions - Irshad Ahmad; Muhammad Kamran; Wennan Su; Wang Haiqi; Shahzad Ali; Bayasgalan Bilegjargal; Shakeel Ahmad; Tiening Liu; Tie Cai; Qingfang Han (Journal of Plant Growth Regulation, 2019)

Seed filling in maize and hormones crosstalk regulated by exogenous application of uniconazole in semiarid regions - Irshad Ahmad; Muhammad Kamran; Shahzad Ali; Tie Cai; Bayasgalan Bilegjargal; Tiening Liu; Qingfang Han (Environmental Science and Pollution Research, 2018)

Application of paclobutrazol: a strategy for inducing lodging resistance of wheat through mediation of plant height, stem physical strength, and lignin biosynthesis - Muhammad Kamran; Irshad Ahmad; Xiaorong Wu; Tiening Liu; Ruixia Ding; Qingfang Han (Environmental Science and Pollution Research, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

De novo assembly of transcriptome from Rhododendron latoucheae Franch. using Illumina sequencing and development of new EST-SSR markers for genetic diversity analysis in Rhododendron - Wen Xing; Juyang Liao; Mengying Cai; Qingfang Xia; Yan Liu; Wen Zeng; Xiaoling Jin (Tree Genetics & Genomes, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)